2021
DOI: 10.3389/fspas.2021.695966
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Remote-Sensing Techniques to Reveal Stealth Coronal Mass Ejections

Abstract: Eruptions of coronal mass ejections (CMEs) from the Sun are usually associated with a number of signatures that can be identified in solar disc imagery. However, there are cases in which a CME that is well observed in coronagraph data is missing a clear low-coronal counterpart. These events have received attention during recent years, mainly as a result of the increased availability of multi-point observations, and are now known as “stealth CMEs.” In this work, we analyze examples of stealth CMEs featuring var… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…In particular, we have exploited the improved capabilities of SDO/AIA with respect to its predecessors to identify weak LCSs that might be linked to the ICME that directly caused the specific problem geomagnetic storm under analysis. As in Nitta and Mulligan (2017) and Palmerio et al (2021b), we found elusive LCSs to be more evident in difference images with long temporal separations that take into account the slow nature of these eruptions. We also considered multi-point coronagraph observations, when available, from the STEREO and SOHO spacecraft, to help identify any associated CME.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, we have exploited the improved capabilities of SDO/AIA with respect to its predecessors to identify weak LCSs that might be linked to the ICME that directly caused the specific problem geomagnetic storm under analysis. As in Nitta and Mulligan (2017) and Palmerio et al (2021b), we found elusive LCSs to be more evident in difference images with long temporal separations that take into account the slow nature of these eruptions. We also considered multi-point coronagraph observations, when available, from the STEREO and SOHO spacecraft, to help identify any associated CME.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to these approaches, the members of the ISSI team (see Introduction) have started using other techniques, such as the Multiscale Gaussian Normalization technique (Morgan and Druckmüller 2014) to enhance lower level signals of the low coronal signatures of CMEs (Alzate and Morgan 2017;O'Kane et al 2019), and the Graduated Cylindrical Shell model (Thernisien et al 2006(Thernisien et al , 2009Thernisien 2011) that gives the 3D trajectory of a CME that may be traced back to the initiation site. The usefulness of these tools for understanding stealthy CMEs is evaluated in a separate paper (Palmerio et al 2021b).…”
Section: Low Coronal Signaturesmentioning
confidence: 99%
“…The CME was also observed by the C2 and C3 telescopes part of the Large Angle and Spectrometric Coronagraph (LASCO; Brueckner et al 1995) onboard the Solar and Heliospheric Observatory (SOHO; Domingo et al 1995) near Earth, but as a much fainter event to the west of the solar disc (Figure 1(g)). The observing geometry of the CME in white light unambiguously indicates that the eruption originated from the Earth-facing Sun; however, inspection of data from the Atmospheric Imaging Assembly (AIA; Lemen et al 2012) instrument onboard the Solar Dynamics Observatory (SDO; Pesnell et al 2012) orbiting Earth reveals no clear eruptive signatures on the disc (Figure 1(e)), even when difference images with long temporal separations are used (see Palmerio et al 2021). Nevertheless, off-limb imagery from the Extreme UltraViolet Imager (EUVI) onboard STEREO-A (Figure 1(a)) un-veils a dynamic, multi-stage eruption scenario.…”
Section: Overview Of the Eruptionmentioning
confidence: 99%
“…We set the CME to maintain a constant speed of 30 km•s −1 until the front arrives to 4 R , at which point it begins to linearly accelerate until reaching 350 km•s −1 at 20 R . This is done to emulate the slow liftoff and early evolution of the eruption in the lower corona observed by COR1 and that is characteristic of stealth CMEs (e.g., Palmerio et al 2021). The resulting full coronal evolution happens over ∼33 hours, which is a typical duration for streamer-blowout CMEs (Vourlidas & Webb 2018).…”
Section: Osprei Model Setupmentioning
confidence: 99%
“…Having no direct association with solar active regions, flares, and/or filaments, SBO-CMEs often lack classic low-coronal signatures (Robbrecht et al, 2009;Ma et al, 2010;Kilpua et al, 2014;Lynch et al, 2016) and are hence characterised as 'stealth CMEs' (Robbrecht et al, 2009;Howard and Harrison, 2013). Recent high-resolution, multi-wavelength, and multi-viewpoint coronal observations have revealed weak low-coronal dynamics associated with stealth CMEs, in some cases enabling study of their formation and lift-off (Korreck et al, 2020;O'Kane et al, 2021;Palmerio et al, 2021b). Stealth CMEs may also cause significant magnetic storms at Earth that are problematic for space weather forecasting (Nitta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%